Gel dressing based on type I collagen modified with oligourethane and silica for skin wound healing. (1st July 2022) - Muñoz-González, Pedro U; Lona-Ramos, María C; Gutiérrez-Verdín, Luis D; Luévano-Colmenero, Guadalupe H; Tenorio-Rocha, Fernando; García-Contreras, René; González-García, Gerardo; Rosillo-de la Torre, Argelia; Delgado, Jorge; Castellano, Laura E; Mendoza-Novelo, Birzabith
Abstract: Cutaneous wound healing is a complex process that leads the skin reparation with the formation of scar tissue that typically lacks skin appendages. This fact drives us to find new strategies to improve regenerative healing of the skin. This study outlines, the contribution of colloidal silica particles and oligourethane crosslinking on the collagen material properties and the effect on skin wound healing in rats. We characterized the gel properties that are key for in-situ gelation, which is accomplished by the latent reactivity of oligourethane bearing blocked isocyanate groups to crosslink collagen while entrapping silica particles. The swelling/degradation behavior and the elastic modulus of the composite gel were consistent with the modification of collagen type I with oligourethane and silica. On the other hand, these gels were characterized as scaffold for murine macrophages and human stem cells. The application of a composite gel dressing on cutaneous wounds showed a histological appearance of the recovered skin as intact skin; featured by the epidermis, hair follicles, sebaceous glands, subcutaneous adipose layer, and dermis. The results suggest that the collagen-based composite dressings are promising modulators in skin wound healing to achieve a regenerative skin closure with satisfactory functional and aesthetic scars.